Desiccation and Mortality Dynamics in Seedlings of Different European Beech (Fagus sylvatica L.) Populations under Extreme Drought Conditions - Bolte, Andreas; Czajkowski, Tomasz; Cocozza, Claudia; Tognetti, Roberto; de Miguel, Marina; Pšidová, Eva; Ditmarová, Ĺubica; Dinca, Lucian; Delzon, Sylvain; Cochard, Hervè; Ræbild, Anders; de Luis, Martin; et al. (Frontiers in Plant Science, 2016)
European beech (Fagus sylvatica L., hereafter also beech), one of the major native tree species in Europe, is known to be drought sensitive. Thus, the identification of critical thresholds of drought impact intensity and duration are of high interest for assessing the adaptive potential of European beech to climate change in its native range. In a common garden experiment with one-year-old seedlings originating from central and marginal origins in six European countries (Denmark, Germany, France, Romania, Bosnia-Herzegovina, Spain), we applied extreme drought stress and observed desiccation and mortality processes among the different populations and related them to plant water status (predawn water potential, ΨPD) and soil hydraulic traits. For the lethal drought assessment, we used a critical threshold of soil water availability that is reached when 50% mortality in seedling populations occurs (LD50SWA). We found significant population differences in LD50SWA (10.5% to 17.8%), and mortality dynamics that suggest a genetic difference in drought resistance between populations. The LD50SWA values correlate significantly with the mean growing season precipitation at population origins, but not with the geographic margins of beech range. Thus, beech range marginality may be due more to climatic conditions than to geographic range, only. The outcome of this study suggests the genetic variation has a major influence on the varying adaptive potential of the investigated populations.